533 Fracture patterns in young children after motor vehicle crashes. (1st September 2016) - Wilson, Michael; Ramphal, Winesh; Dijk, Monique van; Numanoglu, Alp; As, Arjan B van
Abstract : Background: In Africa, road traffic injuries rank second to interpersonal violence and the road traffic fatality rate is higher than for any WHO region. The aim of this study is to explore potential differences in number and patterns of fractures between childhood survivors and non-survivors after a motor vehicle crash in view of developing targeted and more effective prevention strategies. Methods: Total body radiographs were obtained of all children under 13 years presenting to our trauma unit after a motor vehicle crash during a 30 month period between January 2010 and July 2012. In addition, total body radiographs were obtained from the mortuary of all children under the age of 13 who demised after a motor vehicle crash. The number and types of fractures as well as any other skeletal malformations were compared and evaluated. Approval was obtained from our University Ethics Committee. Results: A total of 1045 children were assessed; 1007 presenting to the trauma unit, and 38 directly to the mortuary. Twenty patients presenting to the trauma unit did not survive. The total amount of non survivors was 58 but 6 were excluded since radiographs were not available. From the 987 survivors 79 were excluded because the radiographs were unavailable. The average age of children was 6.2 years (SD 3.1; Range 0–12). Fractures were far more common in non-survivors than survivors (78.8% vs 46.7%). Fractures of the Skull (p < 0.0001), Cervical Spine (p < 0.0001), Thoracic Vertebrae (p < 0.0001), Trunk including Shoulder (p < 0.0001), Lower Arm (p < 0.002), Upper Arm (p < 0.3) were statistically significantly more frequent in non-survivors than in survivors. Fractures of Facial bones, Elbow, Wrist, Hand, Pelvis, Femur, Knee, Foot and Ankle were different but not statistically significant in survivors and non-survivors. Conclusions: This is the first study documenting and comparing fracture patterns with outcome (survivors and non-survivors) in young children after motor vehicle crash. Since motor vehicle crashes are the most common cause of unnatural childhood death it is important to study fracture patterns in order to understand the injury mechanism and develop preventative strategies. This study indicates that skull, cervical spine and torso fractures are more intricately associated with severe morbidity and mortality in children than fractures of other body regions. The upper torso, head and neck are the body regions most vulnerable in young children and requiring most protection.